Social Media and Its Role in Improving Business Performance - Johni S Pasaribu (Greenation Research & Yayasan Global Resarch National, 2023)
Since the early 2000s, Internet technology has significantly influenced various aspects of people's lives around the world. Social media technology is one of the most recent examples of the ongoing interaction between humans and technology that is transforming society. Li and Bernoff use the term “groundswell” to describe social trends, in which people use social media technology to get the information they want from other social media users, not from ordinary professional or public sources. The use of social media has now become a trend and is the most popular digital platform because of its low cost and minimal technical requirements. Social media is not only used by companies as a marketing medium, but is also used to access information about their market, competitors and customers as a tool to improve business performance and innovation. Furthermore, social media is an external means of communication in customer relations. The purpose of this study is to identify the factors that encourage business owners to adopt social media in their business besides knowing what benefits are expected to be obtained when using it. Furthermore, this research explores the perceived benefits and risks of using social media in business. The results of this study prove that social media is very useful for business owners in promoting products, reducing marketing costs, improving relationships with consumers, expanding market share, and gaining access to information for product development purposes.